Preparation of Graphene Oxide Coatings onto Carbon Fibers by Electrophoretic Deposition for Enhancing Interfacial Strength in Carbon Fiber Composites. Issue 5 (28th January 2016) - Jiang, Jianjun; Yao, Xuming; Xu, Chumeng; Su, Yang; Deng, Chao; Liu, Fa; Wu, Jianjun
Abstract : Graphene oxide (GO) were utilized to improve the interfacial performance of carbon fiber (CF) and epoxy resin. An effective way to prepare graphene oxide/carbon fiber hybrid fiber was proposed by the treatment with hydrogen peroxide and concentrated nitric acid combined with electrophoretic deposition process. A characterization of the fiber surface properties was done before and after coating (surface morphologies, surface chemistry, and surface energy). Results showed that a uniform and thick graphene oxide films were tightly attached on the surface of carbon fiber. Moreover, surface wettability of carbon fibers to epoxy resin is significant improved by enhanced surface free energy due to the deposition of GO. Meanwhile, the introduction of GO in the carbon fiber/epoxy resin composites results in a 55.6% enhancement in the interlaminar shear strength, measured by short beam shear tests. Such a fabrication process is simple and effective, without complex chemical reactions and long processing time, and can be a continuous one for industrial scale.